Analisis Pengaruh Kesukesan Sistem Informasi Mahasiswa Menggunakan Model DeLone and McLean - Irvan Bagus Satriya; Tri Lathif Mardi Suryanto; Eristya Maya Safitri (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2023)
University of Hayam Wuruk Perbanas Surabaya's Student Information System (SIMAS) is an online-based information system designed to meet the various minimum requirements needed in lecture information processing activities, starting from the process of collecting, inputting, and processing data on academic information systems. In operation, some information is often not updated quickly, such as when entering a thesis title but does not appear when searching for data. This study aims to measure the factors that influence the success of SIMAS and examine the relationship between variables on net benefits. The research model used is the Information System Success Model 2003, with six measurement variables, namely: information quality, system quality, service quality, intention to use, user satisfaction, and net benefits. The research involved 304 active students as respondents. The results showed that the information quality and user satisfaction variables were significant for the intention to use variable, while the information quality and system quality variables were significant for the user satisfaction variable, the system quality variable and the user satisfaction variable were significant for the net benefits variable.Keywords: Information system success model; Net benefit, DeLone and McLean AbstrakSistem Informasi Mahasiswa (SIMAS) Universitas Hayam Wuruk Perbanas Surabaya merupakan sistem informasi berbasis online yang dirancang untuk memenuhi berbagai persyaratan minimum yang dibutuhkan dalam kegiatan pengolahan informasi perkuliahan, mulai dari proses pengumpulan, input, dan pengolahan data pada sistem informasi akademik. Dalam pengoperasiannya, beberapa informasi sering tidak ter-update secara cepat, seperti pada saat memasukkan judul skripsi namun tidak muncul ketika di lakukan pencarian data.  Penelitian ini bertujuan untuk mengukur faktor-faktor yang mempengaruhi kesuksesan SIMAS dan menguji hubungan antar variabel terhadap net benefit. Model penelitian yang digunakan adalah Information System Success Model 2003, dengan enam variabel pengukuran yaitu: information quality, system quality, service quality, intention to use, user satisfaction, dan net benefist. Penelitian melibatkan 304 mahasiswa aktif sebagai responden. Hasil penelitian menunjukkan variable information quality dan user satisfaction signifikan terhadap variable Intention to use, sedangkan variable information quality dan variable system quality signifikan terhadap variable user satisfaction, variable system quality dan variable user satisfaction signifikan terhadap variable net benefits.